1996
DOI: 10.1002/hep.510240531
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine Green Elimination Test in Orthotopic Liver Recipients

Abstract: perioperative period is needed; however, conventional liver Objective. To determine its predictive capability on function tests have limited reliability 3,4 and the results of graft quality and resultant clinical outcome, the indocyvarious quantitative liver function tests have been conflictanine green (ICG) elimination test was performed by a ing. 5-10spectrophotometric method and a noninvasive fingerRecently, the indocyanine green (ICG) elimination test has piece method with 50 orthotopic liver transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 30 publications
1
51
0
Order By: Relevance
“…Collectively, while these data suggest that bile acid is synthesized and secreted, it would be important to confirm the presence of bile acids via HPLC analysis. Uptake and efflux of ICG is clinically used to evaluate liver functions [38,39]. The monolayer HLC showed uptake of ICG and complete efflux occurred within 24 h. A similar profile in the uptake and efflux of ICG was also seen with the encapsulated HLC.…”
Section: Properties Of Encapsulated Hepatocyte-like Cells 871mentioning
confidence: 76%
“…Collectively, while these data suggest that bile acid is synthesized and secreted, it would be important to confirm the presence of bile acids via HPLC analysis. Uptake and efflux of ICG is clinically used to evaluate liver functions [38,39]. The monolayer HLC showed uptake of ICG and complete efflux occurred within 24 h. A similar profile in the uptake and efflux of ICG was also seen with the encapsulated HLC.…”
Section: Properties Of Encapsulated Hepatocyte-like Cells 871mentioning
confidence: 76%
“…Therefore, ICG elimination has been used to evaluate hepatic blood flow and liver function in liver transplant recipients, after partial hepatectomy in rats, and in septic patients with hepatocellular dysfunction. [15][16][17][18] In addition, ICG is an intravascular marker because it binds to plasma proteins rapidly and completely, impeding its extravascular distribution. Thus, it can be used to estimate both blood volume and cardiac output (CO).…”
mentioning
confidence: 99%
“…21 Previous studies have shown that the ICG elimination test is a reliable indicator of graft quality and subsequent graft outcome early after liver transplantation. [22][23][24] Our threshold value of 10% per minute corresponds to the values predicting far worse outcome in previous studies. [22][23][24] ICG elimination by the liver reflects liver blood flow and microcirculation, hepatocyte energy status, and the inhibition of expression and function of hepatocellular transport systems 21,25 that mediate hepatic uptake and biliary excretion of bile salts and various nonbile salt organic anions such as bilirubin and ICG.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Our threshold value of 10% per minute corresponds to the values predicting far worse outcome in previous studies. [22][23][24] ICG elimination by the liver reflects liver blood flow and microcirculation, hepatocyte energy status, and the inhibition of expression and function of hepatocellular transport systems 21,25 that mediate hepatic uptake and biliary excretion of bile salts and various nonbile salt organic anions such as bilirubin and ICG. 25 The marked increase in PDR ICG and decrease of serum bilirubin levels in survivors compared with nonsurvivors in our study is most likely caused by the restoration of energy metabolism and disappearance of ischemia-reperfusion-induced inhibition of expression and function of hepatocellular transport systems in survivors.…”
Section: Discussionmentioning
confidence: 99%